Dukungan Instrumental Terhadap Kesehatan Mental Remaja Korban Toxic Relationship di Platform Instagram - Nindi Nadia; Ati Kusmawati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Dating during adolescence is considered normal, because you can get to know each other's character in the hope that it will progress to a more serious level. However, this hope is not always fulfilled by everyone, because when they are dating, violence occurs, which is called a toxic relationship. Having a toxic relationship can cause a person to have mental health problems, which can result in someone not being confident and isolating themselves from their surroundings. So, strong support is needed, such as instrumental support, which is direct and real support so that someone can be confident in carrying out daily activities. The aim of this research is to find out whether instrumental support influences the mental health of adolescent victims of toxic relationships on the Instagram platform and how instrumental support influences the mental health of adolescent victims of toxic relationships on the Instagram platform. This research used quantitative methods with 99 samples. The results of the research found show that there is an influence of instrumental support on the mental health of teenagers who are victims of toxic relationships, with a value of 0.994 which shows a positive value, this can be interpreted as an addition of 1% for each. So that Instrumental Support on Mental Health of adolescents obtained an influence level of 0.417 or it can be interpreted that the influence of Instrumental Support on Mental Health was 41.7% and the remaining 58.3% was influenced by other factors not included in this research.